2015
DOI: 10.1111/1754-9485.12417
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of diffusion‐weighted MRI in the differentiation of all liver hydatid cyst types

Abstract: Diffusion-weighted imaging may be useful for providing additional data to determine the type of HC, and for differentiating types CE1, CE2 and CE3 from types CE4 and CE5.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 27 publications
1
5
0
1
Order By: Relevance
“…Similar to our study, Koken et al (17) suggested that a comparison of hydatid cyst types according to ADC values could be beneficial in the differentiation of type 1, 2, and 3 from type 4 and 5.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Similar to our study, Koken et al (17) suggested that a comparison of hydatid cyst types according to ADC values could be beneficial in the differentiation of type 1, 2, and 3 from type 4 and 5.…”
Section: Discussionsupporting
confidence: 89%
“…Koken et al (17) study investigated 92 lesions of 54 patients by creating ADC maps using b50, b500, and b1000 values. When the ADC values were compared according to lesion groups, there was no significant difference between type 1 and 2, 3; type 2 and 3; type 3 and 4; or type 4 and 5.…”
Section: Discussionmentioning
confidence: 99%
“…The size of a SLC is usually < 1 cm but can grow up to 30 cm according to reports in the literature (21). In two studies with 92 and 136 HC lesions, the mean cyst sizes were 7.2 AE 3.6 cm (range ¼ 2.05-21.6 cm) and 7.1 AE 3.1 cm, respectively (20,22). In our study, mean size of the SLCs and type I HCs were found to be 2.59 AE 1.23 cm (range ¼ 1.2-7.6 cm) and 7.49 AE 2.95 cm (range ¼ 2.8-14 cm), respectively.…”
Section: Discussionmentioning
confidence: 96%
“…In previous studies, apparent diffusion coefficient (ADC) values obtained at diffusion-weighted MRI (DWI) were evaluated for the discrimination of subgroups of HCs (14)(15)(16)(17)(18)(19)(20). Only a few studies with a limited number of cases aimed to evaluate the efficiency of ADC values on differentiation of type I HCs and SLCs (15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…Die Datenlage zum Stellenwert der Diffusionswichtung ist heterogen. Der ADC-Wert von inaktiven Zysten ist kleiner als der von aktiven Zysten [23]. Eine Differenzierung von WHO-CE1 Zysten und blanden dysontogenetischen Leberzysten dürfte mit der DWI nicht möglich sein [24].…”
Section: Hinweise Zur Mrt-technikunclassified